Student's perceptions of flipped classroom approach: results from an educational innovation project - Paula Lopes, Ana (2022)
The Flipped Classroom model is well known and recognized, and its popularity seems to keep increasing. In this pedagogical model, the transmission of conceptual knowledge is left to individual tasks outside the classroom while the contact hours, inside the classroom, are completely opened to problem solving, active and peer-assisted learning. The purpose of this work is to describe an educational innovative experience that began in the academic year 2015-2016 with the University of Malaga's Educational Innovation Project PIE15/174 (UMA), based on Flipped Classroom and gamification in a collaborative system among its students. This project has been renewed and extended over the years, with the integration of more teachers and subjects from both the UMA and the Polytechnic University of Porto, up until the current PIE19/156. Further, the aim is to examine the degree of student satisfaction with the strategies and methodologies applied in class, paying special attention to the general aspects and the level of extension of the pedagogical model in each subject. Some statistical analysis of students' satisfaction with the pedagogical model's application are presented. The results are promising and gratifying for all teachers involved, since these show a high degree of satisfaction with the teaching model and the strategy implementation.